Post-pandemic travel behavior of domestic tourists in the Philippines: A generational analysis - Cerio, Calyd T.; Relucio, Janet A. (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The purpose of this study is to analyze the generational differences and similarities in travel behavior to domestic tourist destinations before and after the pandemic. This study also investigates the factors that influence the likelihood that they will travel after the pandemic. The study employed a quantitative method following a causalcomparative design. The study collected 1,516 responses from domestic tourists in the Philippines and used Chisquare and ANOVA tests to identify statistically significant generational differences. In addition, ordinal logistic regression was used to examine the factors that influence the likelihood of travel after the pandemic. This study looked at four generations: baby boomers, generation X, generation Y, and generation Z, and found significant differences in information source preferences, pre-pandemic destination visit history, likelihood of post-pandemic travel, destination evaluation criteria, and travel activity preferences. The findings indicated that online sources, professional advice, and word of mouth play distinct roles across generations, emphasizing the need for targeted marketing strategies. Tourism practitioners are provided with timely insights derived from empirical research, facilitating a deeper understanding of the evolving behavior of domestic tourists in the post-pandemic era.